Sexual function after proctectomy in patients with inflammatory bowel disease: A prospective study - Antonios Gklavas,; Christofis Kyprianou,; Georgios Exarchos,; Linda Metaxa,; Athanasios Dellis,; Ioannis Papaconstantinou, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Inflammatory bowel diseases (IBD), Crohn’s disease (CD) and ulcerative colitis (UC) show a multifactorial impact on patients’ quality of life, including sexual function (SF). The need for surgical intervention remains high, whereas proctectomy is frequently required in these patients. We tried to evaluate the impact of pelvic dissection during proctectomy in IBD patients’ SF.Materials and Methods: We conducted a prospective study, examining the pre- and postoperative (at 6 months) SF of 57 IBD patients that underwent proctectomy in our surgical department, in the period between 2010 and 2016. The 5-item International Index of Erectile Function (IIEF-5) and the Female Sexual Function Index were our research tools for men and women, respectively. We tried to evaluate the impact of gender, age, type of the disease, and surgical procedure on postoperative outcome.Results: Ileal pouch-anal anastomosis (IPAA) was offered to 45 patients, whereas 12 patients underwent total proctocolectomy with permanent end ileostomy (TPC). Men showed a non-significant improvement in median IIEF-5 score after proctectomy (22.0 vs 23.0, p=0.152). The majority of men had no erectile dysfunction either before (56.4%) or after (51.3%) surgery (p=0.599). Changes remained insignificant for subgroup analysis according to age, disease and surgical procedure. Female patients had also a non-significant improvement in overall median score (23.0 vs 24.1, p=0.856). Women’s score remained below the cut-off value of 26.5 for almost every subgroup analyzed.Conclusions: Proctectomy did not affect SF of IBD patents six months after surgery. Female patients seem to face more frequently a poor SF compared to men.Cite this article as: Gklavas A, Kyprianou C, Exarchos G, Metaxa L, Dellis A, Papaconstantinou I. Sexual function after proctectomy in patients with inflammatory bowel disease: A prospective study. Turk J Gastroenterol 2019; 30(11): 943-50.